Semantics of Tradition-Based Bags and Their Application as a Complement to Fashion - Muchlis, Muchlis (Journal La Sociale, 2025)
This study aims to provide an overview of traditional bags in several regions in Indonesia, as well as perceptions (semantics) related to the suitability between shapes and colors when bags (traditional bags) are used with the main clothing as a complement to the fashion. This study uses a qualitative method, where the researcher focuses on understanding and trying to interpret the events that occur along with interaction with the subject from the researcher's point of view. The research techniques carried out are through observation to several related sources, conducting interviews with users and taking documentation for a visual analysis. The conclusion of this study is in the form of a simulation shown through images/visuals by trying to combine the bag with the color that represents the traditional bag when used in the main fashion with various possibilities of visual combinations. The results of the simulation in the form of visual combinations were then cross-checked with data from several related research sources as well as research references about color combinations and then the results became a conclusion from this study.